Extracts and semi-purified fractions of Tagetes patula flowers in the control of root-knot nematodes - Vanessa Marquito Munhoz (Semina: Ciências Agrárias, 2017)
The genus Tagetes constitutes a group of antagonistic plant species that are cytotoxic against plant pathogenic nematodes, with T. patula being particularly efficient. The aim of this study was to evaluate the in vitro effect of extracts and semi-purified fractions of T. patula flowers on eggs and second-stage juveniles (J 2 ) of Meloidogyne incognita, M. javanica, and M. paranaensis , as well as to verify the nematicidal effect of the flavonoids present in T. patula flowers. Extracts and semi-purified fractions were obtained from dried T. patula flowers after maceration and liquidification, yielding crude aqueous (CAE) and crude ethanol-water (CEWE) extracts. Dried flowers were also treated with n -hexane to obtain a crude defatted aqueous extract (CDAE) and a crude ethanol-water defatted extract (CEWDE). Then, the CEWE was fractionated, and the ethyl acetate (EAF), ethanol (EF), methanol (MF), and ethanol:water (EWF) fractions were obtained. CAE, CEWE, CDAE, and CEWDE were tested to evaluate their effects on hatching, mobility, and mortality of J 2 of M. incognita, M. javanica , and M. paranaensis . EAF, EF, MF, and EWF fractions were tested on the same variables of M. incognita . All extracts significantly reduced J 2 hatching of M. incognita, M. javanica , and M. paranaensis when compared to water and water + DMSO. CEWE had nematicidal effects on the three evaluated species, whereas CEWDE demonstrated nematicidal effects against M. incognita and M. javanica , and nematostatic effects on M. paranaensis . This toxic effect showed by CEWE may be related to the high content of quercetin, a major substance present in this sample. It was also observed that EAF accentuated the nematicidal response on Meloidogyne spp., suggesting that other medium polarity (methoxylated) flavonoids act as nematotoxic substances. Thus, these results suggest that quercetin contributes significantly to the nematicidal activity of CEWE and EAF.